A High-Efficiency and Broadband Folded Reflectarray Based on an Anisotropic Metasurface for Generating Orbital Angular Momentum Vortex Beams - Zhen-Yu Yu; Yun-Hua Zhang; Huo-Tao Gao (IEEE Access, 2021)
In this paper, a low-profile folded reflectarray (FRA) assembled by an anisotropic metasurface is proposed to generate high-efficiency and broadband orbital angular momentum (OAM) vortex waves in the Ka band. In order to suppress the mutual coupling and increase the polarization conversion efficiency, a dual-polarization phase matching method (DPPMM) for helical wavefront construction is developed to achieve minimum phase compensation error in the orthogonal direction. A compact subwavelength anisotropic meta-atom with orthogonal $|\big | |$ -shaped structure is designed to achieve flexible wavefront manipulation and high-resolution phase compensation for ${x}$ and ${y}$ -polarization incident waves. After the optimization design, nearly 100% cross-polarization conversion efficiency for the anisotropic metasurface can be achieved at the working frequency of 12 GHz. To validate the proposed design method, an OAM FRA with $24×24$ meta-atoms is fabricated and measured. The measurement results show that the aperture efficiency of the proposed FRA carried with the OAM mode ${l} = 1$ is significantly improved and reaches 20.2%. Moreover, the OAM bandwidth and 3-dB gain bandwidth reach 22.5% and 25%, respectively.